Analisis Penerimaan Sistem Self-Service Kiosk McDonald's Menggunakan Technology Acceptance Model Berdasarkan Kelompok Usia - Revalina Saputera; Yessica Nataliani (Universitas Budi Luhur, 2026)
The fast-food industry continues to adopt digital technology, one example being the implementation of self-service kiosks at McDonald's outlets in Bandung. Although these kiosks are intended to improve service efficiency and reduce dependence on cashiers, their acceptance by users requires further evaluation. This study examines factors influencing user acceptance of self-service kiosks using the Technology Acceptance Model (TAM) and Partial Least Squares Structural Equation Modeling (PLS-SEM). The model comprises Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Attitude Toward Using (ATU), and Behavioral Intention (BI), while Multi-Group Analysis (MGA) compares users aged ≤35 years and >35 years. Data were collected from 100 kiosk users in Bandung through purposive sampling. The findings indicate that PU (β = 0.314) and ATU (β = 0.596) positively and significantly affect BI, whereas PEOU influences BI indirectly through PU and ATU. The structural model explains 78.6% of the variance in behavioral intention. In addition, MGA reveals no significant differences between the two age groups. These findings suggest that age does not substantially influence user acceptance of self-service kiosks in Indonesian fast-food restaurants.